COGNITIVE PROCESS ASSOCIATED WITH CREATIVITY SCALE AND CREATING BUSINESS INNOVATIONS THAT AFFECT THE SUCCESS OF BUSINESS ENTREPRENEURS AFTER COVID-19 PANDEMIC - Putsom, Wanlee (Asian Academy of Management Journal, 2025)
Creativity is a crucial skill for business entrepreneurs, particularly in the aftermath of the COVID-19 pandemic. Therefore, the objective of this research is to examine the influence of entrepreneurial creativity using the Cognitive Process Associated with Creativity (CPAC) scale model to examine its influence on business innovation and the success of small business entrepreneurs in the post COVID-19 context according to the concept of CPAC Model as a tool to study, together with, the variables on business innovation and the success of business entrepreneurs. The findings show that the CPAC model positively influences business innovation, which in turn contributes to the success of business entrepreneurs. Thus, the findings of this research suggest that business entrepreneurs need to use creativity so that their performance leads to business innovation and to business success. The results also suggest that the CPAC model be examined in other samples to explore the perspectives of individuals regarding the use of creativity to support the search for leveraging creativity for successful business operations. This research encompasses the CPAC model into entrepreneurship, showing how cognitive processes foster innovation and business success, with both theoretical and practical contributions.